The rise and fall of worldwide income inequality, 1820–2035. (19th May 2020) - Connors, Joseph; Gwartney, James; Montesinos‐Yufa, Hugo
Abstract: The development process and the demographic changes that are a central element of it explain both the nearly two centuries of increasing income inequality prior to 2000 and the reversal of this trend that followed. There are at least four phases of the development process: (1) Malthusian pre‐development, (2) initial growth, (3) improved productivity, and (4) receding growth. Prior to the industrial revolution, the entire world was in the Malthusian Phase 1. During 1820–1950, about 20 countries, mostly in Western Europe, North America, and Oceania, moved out of Phase 1 and began to grow more rapidly. But, per capita income levels in the rest of the world continued to stagnate and worldwide income inequality widened continuously for at least 150 years following the Industrial Revolution. Around 1960, developing countries began to escape the Malthusian trap and move into Phase 2 of development. By the latter part of the 20th century, many developing countries were achieving growth rates equal to or greater than the high‐income countries, slowing the rise in inequality. By 2000–2015 most developing countries were in either Phases 2 or 3 of development, while most of the high‐income countries were moving into Phase 4, leading to a sharp reduction in worldwide income inequality. The recent reductions in worldwide income inequality are likely to continue in the near term because of the continuation of the more favorable demographic changes in developing compared to high‐income countries.